The impact of Flipgrid on Nigerian undergraduates' speaking skills and speaking anxiety - Ahmed Tanimu Jibril; Muhammad Mukhtar Aliyu; Halima Sadiya Yakubu; Ummu-Kaltume Aminu (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2024)
Despite being the medium of instruction at all levels of education, English fluency remains a challenge for many Nigerian undergraduates, especially considering English functions as a second language in the country. This highlights the need for effective learning strategies for undergraduates. Hence, this study investigated the potential of Flipgrid, a video-based discussion platform, to improve speaking skills and reduce speaking anxiety among Nigerian undergraduates. The study employed a pre- and post-quasi-experimental research design and selected a class of 25 third-year undergraduates at a university in Nigeria as participants. The study results reveal a significant positive impact of the Flipgrid platform on the participants' speaking skills in fluency, pronunciation and accent, vocabulary, accuracy, and comprehension. The study also found a significant reduction in participants' speaking anxiety post-intervention. The results suggest that the platform not only contributes to skill development but also plays a crucial role in overcoming anxiety related to the studentâ€™s oral communication. Therefore, the study recommends the integration of Flipgrid into English language teaching as a valuable tool for improving Nigerian undergraduates' speaking proficiency and reducing speaking anxiety. Additionally, the study suggests further research to explore the long-term effects of the Flipgrid platform on language learning in different contexts.Â